2021
DOI: 10.3390/v13091674
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of Organogermanium Compound THGP on RIG-I-Mediated Viral Sensing and Viral Replication during Influenza a Virus Infection

Abstract: The interaction of viral nucleic acid with protein factors is a crucial process for initiating viral polymerase-mediated viral genome replication while activating pattern recognition receptor (PRR)-mediated innate immune responses. It has previously been reported that a hydrolysate of Ge-132, 3-(trihydroxygermyl) propanoic acid (THGP), shows a modulatory effect on microbial infections, inflammation, and immune responses. However, the detailed mechanism by which THGP can modify these processes during viral infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It has been also reported that Ge-132 suppresses influenza virus growth and reduces mouse mortality [ 34 ]. Most recently, it was revealed that THGP has dual effects in suppressing the growth of influenza virus A and the development of pneumonia by directly binding to the 5′-triphosphate RNA of influenza virus A [ 35 ]. SARS-CoV-2, unlike influenza virus, was not found to interact with THGP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that Ge-132 suppresses influenza virus growth and reduces mouse mortality [ 34 ]. Most recently, it was revealed that THGP has dual effects in suppressing the growth of influenza virus A and the development of pneumonia by directly binding to the 5′-triphosphate RNA of influenza virus A [ 35 ]. SARS-CoV-2, unlike influenza virus, was not found to interact with THGP.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive study of the various biological activities of Ge-132 [ 8 ], including those that were previously known [ 36 ], particularly its antitumor [ 78 , 79 , 80 , 81 , 82 , 83 , 84 ] and immunomodulating [ 43 , 52 , 54 , 85 ] activities, also continued. In addition, Ge-132 is proposed as a treatment for a number of diseases: haemorrhagic and ischemic stroke [ 86 , 87 ], viral infections [ 43 , 54 , 88 , 89 , 90 ] (including COVID-19 [ 43 ]), various inflammatory diseases, particularly mastitis [ 4 ]. Next, this is suggested in the treatment of diabetes mellitus to reduce insulin resistance [ 91 ], and as an antioxidant for various disorders caused by oxidative stress [ 53 , 54 , 92 , 93 , 94 ] as well as in dermatological practice to heal skin wounds and protect the skin from reactive oxygen species [ 95 , 96 ].…”
Section: Organic Germanium Compoundsmentioning
confidence: 99%
“…In addition, Ge-132 is proposed as a treatment of a number of diseases: haemorrhagic and ischemic stroke [91,92], viral infections [43,54,[93][94][95] (including COVID-19 [43]), various inflammatory diseases, in particular mastitis [4]. Next, it is suggested in the treatment of diabetes mellitus to reduce insulin resistance [96], and as an antioxidant for various disorders caused by oxidative stress [53,54,[97][98][99] as well as in dermatological practice to heal skin wounds and protect the skin from reactive oxygen species [100,101].…”
Section: Germanium Sesquioxidesmentioning
confidence: 99%